ROLE OF TECHNOLOGICAL ADVANCEMENTS IN CONSUMER BEHAVIOUR FOR ELECTRICAL HOUSEHOLD EQUIPMENT IN DHARMAPURI DISTRICT - Senthilkumar, V.; Sathiya, V. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Technological advancements have revolutionized consumer behavior, particularly in the electrical household equipment sector. In Dharmapuri District, evolving technologies such as energy-efficient appliances, smart features, and innovative designs have influenced purchasing patterns. Consumers now prioritize their convenience, durability, and eco-friendliness while making decisions. This study explores the role of these technological advancements in shaping preferences, evaluating their impact on factors such as product selection, brand loyalty, and overall satisfaction. Using empirical data collected from consumers behaviour in Dharmapuri, this study identifies key trends and provides insights into how manufacturers and retailers can leverage technology to cater to evolving needs.